A Comparative Study of Inter-Provincial Inclusive Economic Growth in Indonesia 2010-2015 with Approach Methods of ADB, WEF, and UNDP - Agnes Vera Yanti Sitorus; Ade Marsinta Arsani (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2018)
Economic growth is the most widely used measure of economic activity. Indonesia as one of G-20 has positive economic growth while the global economic downturn. Nevertheless, income inequality rises from 0,363 in 2005 to 0,394 in 2016. High growth GDP does not guarantee that all persons will benefit equally. GDP has limitation in reflection the distribution of income, social and economic progress. Therefore, it takes more than economic growth to ensure that the growth of economic activity can be obtained by all levels of society. This study uses three main references to measure the inclusiveness of economic growth, namely techniques introduced by United Nation Development Programme (UNDP), Asian Development Bank (ADB), and World Economic Forum (WEF). The results of this study indicate that the measurement of inclusive economies in Indonesia generally shows satisfactory results. If different techniques approached is applied, there is a difference in the status of inclusiveness in 33 provinces and still inequalities in some variables mainly occur in infrastructure, education, and income. Therefore, program priority is needed to deal with that problems.